A Muscle-Centric Perspective on Intermittent Fasting: A Suboptimal Dietary Strategy for Supporting Muscle Protein Remodeling and Muscle Mass? - Williamson, Eric; Moore, Daniel R. (Frontiers in Nutrition, 2021)
Muscle protein is constantly ‘turning over’ through the breakdown of old/damaged proteins and the resynthesis of new functional proteins, the algebraic difference determining net muscle gain, maintenance, or loss. This turnover, which is sensitive to the nutritional environment, ultimately determines the mass, quality and health of skeletal muscle over time. Intermittent fasting has become a topic of interest in the health community as an avenue to improve health and body composition primarily via caloric deficiency as well as enhanced lipolysis and fat oxidation secondary to an attenuated daily insulin response. However, this approach belies the established anti-catabolic effect of insulin on skeletal muscle. More importantly, muscle protein synthesis, which is the primary regulated turnover variable in healthy humans, is stimulated by the consumption of dietary amino acids, a process that is saturated at a moderate protein intake. While limited research has explored the effect of intermittent fasting on muscle related outcomes, we propose that infrequent meal feeding and periods of prolonged fasting characteristic of models of intermittent fasting may be counter-productive to optimizing muscle protein turnover and net muscle protein balance. The present commentary will discuss the regulation of muscle protein turnover across fasted and fed cycles and contrast it with studies exploring how dietary manipulation alters the partitioning of fat and lean body mass. It is our position that intermittent fasting likely represents a suboptimal dietary approach to remodel skeletal muscle, which could impact the ability to maintain or enhance muscle mass/quality, especially during periods of reduced energy availability.